2016
DOI: 10.1017/s0007114515005449
|View full text |Cite
|
Sign up to set email alerts
|

Zinc as an adjunct to antibiotics for the treatment of severe pneumonia in children <5 years: a meta-analysis of randomised-controlled trials

Abstract: The effect of Zn, as an adjunct to antibiotics, on the treatment of severe pneumonia in young children is still under debate; therefore, we performed a meta-analysis to evaluate the therapeutic role of Zn for severe pneumonia in children younger than 5 years. PubMed, Cochrane library and Embase databases were systematically searched from inception until October 2015 for randomised-controlled trials (RCT) that assessed the effect of Zn as an adjunct to antibiotics for severe pneumonia. Random-effects model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Our findings are largely concordant with previous meta-analyses. [20][21][22][23] In difference to Wang and Song, 23 we did not find decreased mortality in the zinc supplementation group. The study by Srinivasan et al 32 with high risk of bias in outcome reporting was driving the results presented by Wang and Song and neither of the two new large studies published since then showed any increased risk of mortality.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Our findings are largely concordant with previous meta-analyses. [20][21][22][23] In difference to Wang and Song, 23 we did not find decreased mortality in the zinc supplementation group. The study by Srinivasan et al 32 with high risk of bias in outcome reporting was driving the results presented by Wang and Song and neither of the two new large studies published since then showed any increased risk of mortality.…”
Section: Discussioncontrasting
confidence: 83%
“…However, the role of adjunctive zinc at presentation in pneumonia is still controversial: meta-analyses published in 2011, 2012 and 2016 [20][21][22] found no effect, while another published in 2018 estimated a significant reduction in mortality (risk ratio 0.43, 95% CI 0.22 to 0.83), but no difference in composite treatment failure rates. 23 The last study was published in 2018 and included studies up to October 2015, 4 years before our search.…”
Section: Resultsmentioning
confidence: 99%
“…However, in a stratified analysis, the reduction in mortality was limited to HIV infected children. A recent meta-analysis of nine zinc supplementation trials, as an adjunct treatment of severe pneumonia, did not show any benefit in time to recovery, length of hospital stay, treatment failure or change of antibiotics [ 32 ]. It is also possible that the low specificity of the WHO definition of severe pneumonia may have contributed to the study’s negative result as a lack of specificity in the diagnostic criteria for measuring study outcomes biases the risk/rate ratio towards null values.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the common cold may be reduced in adults and children after administration of zinc >75 mg/day, but not at lower doses; the type of zinc salt used can also have an effect, with greater benefits with zinc acetate compared with other zinc salts (mostly high-quality studies) [219]. However, zinc (10-20 mg/day) had no significant effect on pneumonia in children, failing to reduce the time to recovery from severe pneumonia [220,221], duration of hospital stay [220][221][222], time to clinical recovery [222], or time to recovery from the effects of severe pneumonia including tachypnoea and chest indrawing (all low-to-moderate evidence) [221,222].…”
Section: Micronutrients In the Management Of Acute Infectionsmentioning
confidence: 99%